Struttura della proposizione e ontologia. Suggerimenti per possibili ricerche - Di Prospero, Alfonso (Philosophy Kitchen - Rivista di filosofia contemporanea, 2017)
The purpose of this paper is to explore the theoretical possibilities that are offered by the inquire concerning the rules that describe the functioning of proposition, in order to analyse our intuitions about ontology. The hypothesis that is presented is that the structure of “proposition” (that is organized in “topic” and “comment”) shapes our thought pushing us to believe that it is true a kind of ontology that is akin to Aristotle’s belief that “substance” and “accident” are central concepts in the correct view of Metaphysics. The following remarks aim to give some suggestions that can be useful to deepen such a kind of perspective with reference to Wittgenstein’s Tractatus logico-philosophicus.